5/(1+x) = 3 – 4/(x-1)

5/(1+x) = 3(x-1)/x-1 – 4/(x-1)

5/(1+x) = (3x– 7)/(x-1)

5(x-1)/(1+x)(x-1) = (3x– 7)(1+x)/(x-1)(1+x)

(5x-5)/(x-1+x^2-x) = (3x+3x^2-7-7x)/(x-1+x^2-x)

5x-5 = 3x^2 - 7 - 4x

(3x^2 - 9x – 12)/3 = 0

x^2 – 3x – 4 = 0

x = - (3/2) ± √ (3/2)^2 + 4

x = -1,5 ± √ 6,25

x = -1,5 ± 2.5

x1 = 1

x2 = -4

Answer is suppost to be

x1 = -0,21

x2 = 3,21

Where did I go wrong? :D

Guest May 6, 2017

#1**+2 **

Solve for x:

5/(x + 1) = 3 - 4/(x - 1)

Bring 3 - 4/(x - 1) together using the common denominator x - 1:

5/(x + 1) = (3 x - 7)/(x - 1)

Cross multiply:

5 (x - 1) = (x + 1) (3 x - 7)

Expand out terms of the left hand side:

5 x - 5 = (x + 1) (3 x - 7)

Expand out terms of the right hand side:

5 x - 5 = 3 x^2 - 4 x - 7

Subtract 3 x^2 - 4 x - 7 from both sides:

-3 x^2 + 9 x + 2 = 0

Divide both sides by -3:

x^2 - 3 x - 2/3 = 0

Add 2/3 to both sides:

x^2 - 3 x = 2/3

Add 9/4 to both sides:

x^2 - 3 x + 9/4 = 35/12

Write the left hand side as a square:

(x - 3/2)^2 = 35/12

Take the square root of both sides:

x - 3/2 = sqrt(35/3)/2 or x - 3/2 = -sqrt(35/3)/2

Add 3/2 to both sides:

x = 3/2 + sqrt(35/3)/2 or x - 3/2 = -sqrt(35/3)/2

Add 3/2 to both sides:

**Answer: | x = 3/2 + sqrt(35/3)/2 or x = 3/2 - sqrt(35/3)/2**

Guest May 6, 2017

#2**+2 **

5/(1+x) = 3 – 4/(x-1)

Answer is suppost to be

x1 = -0,21

x2 = 3,21

Where did I go wrong? :D

\(\frac{5}{1+x}=3-\frac{4}{x-1}\)

\(\frac{5}{1+x}+\frac{4}{x-1}=3\)

\(\frac{5x-5+4+4x}{x^2-1}=3\)

\({9x-1}=3x^2-3\)

\(3x^2-9x-2=0\)

\(x^2-3x-\frac{2}{3}=0\)

\(x_1=1.5+\sqrt{2.25+\frac{2}{3}}\)

\(x=1.5\pm\sqrt{2.91\overline{66}}\)

\(x_1=3.2078\\x_2=-0.2078\)

!

asinus
May 6, 2017